STUDI ABRASI DAN SEDIMENTASI DI PERAIRAN BUA-PASSIMARANNU KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - MARZUKI UKKAS (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2009)
Determination of category abrasion or sedimentation to applies formulation of empiric developed by Sunamura and Horikawa, with height and wavelength, median measure item sediment and coastal gradient as determinant. Current data and tidal applied as the determinant supporter. Waving maximum found at area Bisokeng part of south with height 0,52 metre and long 25,82 metre. Low is found in area Kahukahu with height 0,17 metre and long 8,71 metre. Coastal gradient alongside location of research is met [by] two categories namely flat at area Takkalalla and Muara Sungai Bua, and sloping category at other area. Median measure item the biggest sediment is found in area Bisokeng part of South and smallest at area Marana. Based on the determinant is obtained [by] information that six locations in research area experiences coast abrasion (north Baringeng, south Baringeng, Marana, south Jahung-jahung, north Bisokeng and north stone Ujung). The eight locations is permanent in stable condition (neutral). Result of prediction of coastal stability applies prediction waving it is known that from 61.11% case of wave is enabling the happening of 54,4% coast to experience abrasion, 6,6% remain to be stable and 39% experiences sedimentation.